PEMBARUAN PERADABAN ISLAM DI MESIR - Dewi, Nurfitria; Nizam, Ahmad; Aurman, Aurman; Khairat, Ummil (Borneo : Journal of Islamic Studies, 2025)
This research comprehensively examines the historical range of the Islamic renewal movement in Egypt from the early 19th century to the contemporary era. The main focus of the research is to analyze the transformation of Islamic thought and reform movements that have shaped the social, political, and intellectual landscape of modern Egypt. Through a historical-analytical approach, this research traces various important phases of reform, starting from the modernization of Muhammad Ali Pasha and the emergence of the Salafiyah movement spearheaded by Jamaluddin Al-Afghani and Muhammad Abduh to contemporary dynamics involving various actors and institutions. Research findings show that the Islamic renewal movement in Egypt has experienced significant evolution in response to the challenges of modernity, colonialism, and global socio-political changes. The main contribution of this research is a comprehensive mapping of the dialectic between tradition and modernity in the context of Islamic renewal in Egypt, as well as an analysis of its impact on the development of contemporary Islamic thought in the Muslim world. This research also identifies patterns of continuity and change in the reform movement, which can provide a valuable perspective for understanding the dynamics of Islam and modernity in the contemporary Muslim world.